CULTURE OF SAFETY IN THE FIELD OF CIVIL AVIATION: ADMINISTRATIVE AND LEGAL ASPECTS - Husar, Olga A. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the concept of «culture of safety» in civil aviation is defined and analyzed in the article. Methods: dialectal method of cognition general scientific and special methods are used in this article. Results: the new types of threats for civil aviation have been analyzed, the types of activities carried out by the authorized body in the field of civil aviation for the improvement of the culture of safety in civil aviation are given. The system-forming components of the culture of safety in the field of civil aviation are determined. Discussion: the problems of non-compliance by civil aviation personnel with the norms of aviation legislation, which leads to flight safety and indicates a low level of safety culture in the field of civil aviation; cultural components that affect flight safety management.